Kit I-Ied Model Innovation Student Learning Interest In Islamic Education Study Program - Azhar Kholifah; Alfiani Rif’atus Sholihah (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
The advancement of learning innovation in the 5.0 era is characterized by the integration of modern technologies, such as the Internet of Things and artificial intelligence, as well as big data analysis that focuses on a more personalized and interactive learning experience. In the current context, education in this setting should not only be oriented towards the mastery of material or theory but also be able to develop critical and creative skills, especially in facing global challenges. Project-based learning, collaboration between students, and the combined use of digital platforms are important elements in creating an inclusive and adaptive learning environment. By utilizing this technology, it is expected to increase both effectiveness and efficiency in the learning process and to form work-ready individuals. This research aims to explore one of the learning models in the 5.0 era in an effort to increase interest in learning in higher education by using the Kit I-Ied learning model innovation. The Kit I-Ied learning model innovation is a development of the Kit I-Sir learning model innovation. Kit I-Ied offers the use of learning models by covering three aspects of education, namely cognitive, psychomotor, and affective, with the latest technology in the form of queezezz applications. This research uses a qualitative approach, where data is obtained through interview and observation techniques. The results showed that integrating digital technology, in this case the Kit I-Ied model, as an innovation in the Islamic Education study program was able to increase student interest in learning, as evidenced by the creativity and critical analytical level of students who were enthusiastic about attending lectures. Keywords: Learning Innovation, I-Ied Kit, Islamic Religious Education